Distribution of angiotensin converting enzyme gene polymorphism among Northern Hans, Dahurs, and Ewenks - Zhang Ying-Min; Zhang Li-Ying; Wang Ke-Qiang; Ge Jun-Bo (Acta Pharmacologica Sinica; Vol 22, No 8 (August 2001): Acta Pharmacologica Sinica, 2016)
Aim: To observe the polymorphism of angiotensin-converting enzyme (ACE) gene in Northern Hans, Dahurs, and Ewenkis of China. Methods: The polymerase chain reaction was used to type the insertion/deletion polymorphism at intron 16 of ACE gene among 90 Northern Hans, 84 Dahurs, and 64 Ewenkis individuals. The experiment displayed the distribution in three kinds of ACE genotype: ID (heterozygotes of insertion and deletion), DD (homozygotes of deletion), and II (homozytes of insertion). Results: In Northern Hans the percentages of the distributing ACE I/D genotype were ID 27.8 %, DD 17.8 %, and II 54.4 %. The I/D genotype frequency of Dahurs individuals were ID 60.7 %, DD 26.2 %, and II 13.1 %. The Ewenkis genotype frequency were ID 70.3 %, DD 21.9 %, and II 7.8 %. Conclusion: The polymorphism of ACE gene of Northern Hans is different from that of Dahurs and Ewenkis in China.